(untitled) (Ciencias Veterinarias, 2017)
Milk components provide an economical and less invasive tool to monitor metabolic balance and food rations given to dairy cattle. In order to determine values for fat, protein, protein/fat ratio, and milk urea nitrogen in Costa Rican dairy cows, milk samples were taken from 442 animals from four specialized dairy farms in northern Alajuela and Heredia, during the two daily milkings in April and August 2012. Each component was analyzed using descriptive statistics and comparing means for different categories according to days in lactation, parity number, season of sampling and breed. Average levels were found at 3.34% for protein (95% CI: 3.29-3.37), 4.13% for fat (95% CI: 4.04-4.22), and 16.81 mg/dl for urea nitrogen (95% CI: 16.64-17.26), as well as an average protein/fat ratio of 1.26 (95% CI: 1.24-1.28). There were differences in the components based on breed, parity number and days in lactation. Variations in the percentages of fat, protein, protein/fat ratio and milk urea nitrogen according to breed, parity number, season and days in lactation may indicate metabolic imbalances; consequently, the foregoing must be taken into account when analyzing the diet of cows and their productive and reproductive performance.